Target strength measurement of Nemipterus peronii and Nemipterus japonicus (Perciformes: Nemipteridae) in Aceh, Indonesia - SYAHRUL PURNAWAN; HENRY M. MANIK; TOTOK HESTIRIANOTO; KHAIRUL AMRI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Purnawan S, Manik HM, Hestirianoto T, Amri K. 2025. Target strength measurement of Nemipterus peronii and Nemipterus japonicus (Perciformes: Nemipteridae) in Aceh, Indonesia. Biodiversitas 26: 2992-2999. Threadfin breams (Nemipteridae) are ecologically and commercially important demersal fish in the Indo-Pacific region. Accurate estimation of fish population abundance using hydroacoustic methods depends on species-specific Target Strength (TS) reference values. However, no standardized TS data currently exist for threadfin breams. This study aimed to establish TS reference values for two threadfin bream species, namely Nemipterus peronii (n: 15) and Nemipterus japonicus (n: 13), collected from coastal waters of Aceh, Indonesia. The total length (TL) and weight (W) were measured to determine the length-weight relationship for both species. TS values were measured using a scientific single-beam echosounder operating at a frequency of 200 kHz in a water tank. Nemipterus japonicus showed positive allometric growth, while N. peronii showed negative allometric growth, as evidenced by b values of 3.0628 and 2.1831, respectively. Significant TL-TS relationships (P<0.05) were observed with TS = 46.47 log(TL) ? 104.49 for N. peronii and TS = 22.89 log(TL) ? 72.69 for N. japonicus. Adjusted regression models with a standardized slope of 20 produced intercept values of b20: -70.96 for N. peronii and b20: -68.78 for N. japonicus. The result suggested that even within the same genus, morphological differences led to varying TS values for the same body length. Furthermore, species-specific acoustic survey models were important to improve stock assessment accuracy and contribute to effective fisheries management